Tingkat Stres Berhubungan dengan Kualitas Tidur Santri Kelas X Pondok Modern Al-Aqsha - Rahayuningtyas, Salsha Bila; Nurhakim, Furkon; Setiawan, Setiawan (FORIKES, 2024)
Stress does not depend on age, including teenage students. Stress in adolescent students is influenced by several factors such as biological, psychological and environmental. If stress in students is not treated immediately, other problems will arise that can disrupt psychological and physical health, one of which is fulfilling sleep needs, where the quality of sleep becomes poor. The aim of this research was to analyze the relationship between stress and sleep quality of class X students at Pondok Modern Al-Aqsa, Sumedang. This research used quantitative methods with a cross-sectional design. The research subjects were selected using a total sampling technique from class X students, consisting of 75 female students and 60 male students who were in the dormitory. Stress and sleep quality measurements were carried out using special questionnaires, namely the Perceived Stress Scale (PSS-10) and the Pittsburg Sleep Quality Index (PSQI). Data were analyzed using the Spearman correlation test. The analysis results showed the p value of 0.000. It was concluded that stress levels correlated with the sleep quality of class X students at Pondok Modern Al-Aqsa, Sumedang.Keywords: sleep quality; teenage students; Students; stress ABSTRAK Stres tidak memandang usia, termasuk pada siswa remaja. Stres pada siswa remaja dipengaruhi oleh beberapa faktor seperti biologis, psikologis dan lingkungan. Jika stres pada santri tidak segera ditangani, maka akan muncul masalah-masalah lain yang dapat menganggu kesehatan psikis dan fisik, salah satunya adalah pemenuhan kebutuhan tidur, di mana kualitas tidur menjadi buruk. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara stres dan kualitas tidur santri kelas X di Pondok Modern Al-Aqsha, Sumedang. Penelitian ini menggunakan metode kuantitatif dengan rancangan cross-sectional. Subyek penelitian dipilih dengan teknik total sampling pada santri kelas X, yang terdiri atas 75 santri perempuan dan 60 santri laki-laki yang berada di asrama. Pengukuran stres dan kualitas tidur dilakukan menggunakan kuisioner khusus yaitu Perceived Stress Scale (PSS-10) dan Pittsburg Sleep Quality Index (PSQI). Data dianalisis dengan uji korelasi Spearman. Hasil analisis menunjukkan nilai p = 0,000. Disimpulkan bahwa tingkat stres berkorelasi dengan kualitas tidur santri kelas X di Pondok Modern Al-Aqsha, Sumedang.Kata kunci: kualitas tidur; siswa remaja; santri; stres